2016
DOI: 10.1093/gastro/gow021
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin predicts survival in patients with hilar cholangiocarcinoma

Abstract: Background and aims: Hilar cholangiocarcinoma is a devastating malignancy with incidence varying by geography and other risk factors. Rapid progression of disease and delays in diagnosis restrict the number of patients eligible for curative therapy. The objective of this study was to determine prognostic factors of overall survival in all patients presenting with hilar cholangiocarcinoma.Methods: All adult patients with histologically confirmed hilar cholangiocarcinoma from 2003 to 2013 were evaluated for pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
(18 reference statements)
2
18
0
Order By: Relevance
“…It is reported that approximately 70% of EHC cases have abnormal liver function [27]. Therefore, higher ALBI reflects liver dysfunction and results in poor prognosis in EHC [19]. Secondly, as shown in our study, higher ALBI grade is associated with higher CA19-9 and CRP, both of which are crucial prognostic factors of EHC [18, 28].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is reported that approximately 70% of EHC cases have abnormal liver function [27]. Therefore, higher ALBI reflects liver dysfunction and results in poor prognosis in EHC [19]. Secondly, as shown in our study, higher ALBI grade is associated with higher CA19-9 and CRP, both of which are crucial prognostic factors of EHC [18, 28].…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies on potential prognostic factors of EHC are limited and unsatisfactory. Amongst preoperative ALB, TBIL, CP grade, tumor characteristics, and tumor markers such as CA19-9 and CEA have been established as important prognostic factors [18, 19]. However, the majority of the studies have assessed the prognostic factors only in EHC patients with surgical resection, while most EHC patients present with advanced stage at diagnosis and no curative treatments can be applied [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of liver surgery and other major surgeries have shown that a drop in albumin level correlates with postoperative complications[ 10 ]. Moreover, preoperative serum albumin level has been characterized as an independent factor of recurrence and OS after resection of hepatocellular carcinoma[ 16 ] and of OS in patients with hilar cholangiocarcinoma[ 17 ]. The tumor-like behavior of AE is probably more similar to a cancer such as cholangiocarcinoma than to those cancers frequently related to underlying liver diseases, such as hepatocellular carcinoma which commonly presents with hepatitis and/or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HP was proposed as pronucleating proteins because they were highly expressed in the fast nucleating bile of patients with cholesterol stones [44]. Waghray et al predicted survival in patients with hilar cholangiocarcinoma by serum albumin [45]. C3 and HP were identified as more abundant in cholangiocarcinoma [46].…”
Section: Cholangiocarcinoma Datasetmentioning
confidence: 99%